Efektivitas Intervensi Relaksasi Otot Progresif (ROP) terhadap Penurunan Tingkat Depresi pada Lansia: Case Report Keperawatan - Azhrah Fatimah Ayunurrochim; Nopryan Ekadinata; Muh Fathoni Rohman (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The proportion of the elderly population is increasing every year, and the elderly are experiencing various changes, both in physical, mental and social aspects. The elderly are residents aged over 60 years. Elderly people often experience various psychological problems such as loneliness, isolation, helplessness, lack of self-confidence, post-power syndrome, anxiety disorders and depression. Depression is a mood disorder that can cause prolonged feelings of sadness and persistent loss of interest, characterized by prolonged sadness, mood swings, and lack of interest in activities. The tool used to measure the level of depression in this case report uses the GDS (Geriatric Depression Scale) instrument. In this case report, the results of an assessment of one 66 year old client were obtained with a GDS score of 11 which indicated moderate depression. Management of depression can use pharmacological or non-pharmacological therapy. This case report refers to the Indonesian Nursing Intervention Standards (SIKI) using progressive muscle relaxation (ROP). The ROP intervention was carried out at BPSTW Abiyoso Wisma Talkondo for seven days with three evaluations. The results obtained were that the client experienced a decrease in the level of depression with a score of 5, namely mild depression. It can be concluded that ROP is effective in reducing depression levels in the elderly.